THE EFFECT OF WORD OF MOUTH, PRICE PERCEPTION, BRAND IMAGE AND TRUST ON PURCHASE DECISION USING PURCHASE INTENTION AS AN INTERVENINGVARIABLE (Study at Middle Class Housing in Semarang) - Alvin Gandhi Wijaya; Moch Zulfa (UNISSULA, 2017)
This study aims to analyze the effect of word of mouth, price perception, brand image and trust on purchase intention and to analyze the effect of word of mouth, price perception, brand image, trust and purchase intention upon purchase decision of middle class housing in Semarang. The sample used in this study was 100 people. Techniques used in analyzing the data were descriptive analysis and multiple linear regression analysis. Based on the results of the analysis, it can be concluded that: 1) word of mouth has a significant effect on purchase intention of middle class housing in Semarang, 2) price perception has a significant effect on purchase intention of middle class housing in Semarang, 3) there is a significant effect of brand image upon purchase intention of middle class housing in Semarang, 4) there is a significant effect of trust on purchase intention of middle class housing in Semarang, 5) word of mouth has a significant effect upon purchase decision of middle class housing in Semarang, 6) priceperception gives a significant effect on purchase decision of middle class housing in Semarang, 7) there is a significant effect of brand image upon purchase decision of middle class housing in Semarang, 8) ) there is a significant effect of trust on purchase intention of middle class housing in Semarang, and 9) purchase intention can intervenethe effect of word of mouth, price perception, brand image, trust and buying interest upon purchase decision.Keywords: word of mouth, price perception, brand image, trust, purchase intention, purchase decision